Kepemimpinan Kepala Badan Kepegawaian Daerah Kabupaten Katingan Provinsi Kalimantan Tengah - Leda Almuqsith; Ardiansyah Ardiansyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
In the leadership of an organization, the lead role that determines the effort to achieve the goals of the organization he leads. This implies that the progress of the journey of the life of the organization depends on the extent of the ability of the leader in carrying out his leadership duties. This study uses qualitative methods, which are intended to develop concepts, gather facts by being supported by existing data and used to show and answer whether the problem is true. The data source consists of primary data (1) while the primary data source is the employee of the Regional Personnel Agency of Katingan Regency, Central Kalimantan Province. Data collection techniques are observation, interviews, and documentation. Based on the results of the study, it was found that (1) Leadership of the Regional Civil Service Agency (BKD) of Katingan Regency was able to influence organizational goals, motivate subordinate behavior to achieve goals, influence to improve the group so that the desired goals through vision and mission can be achieved. (2) Head of BKD Regional Personnel Agency, Katingan Regency obtains support and cooperation from people outside the organization to achieve organizational goals that have been previously planned. (3) The success of the Regional Personnel Agency (BKD) of the Katingan district depends on the leadership of the head of the Katingan regency agency itself whether it is able to influence, motivate subordinate behavior and to improve the group